An Alternative Assessment Model to Improve a Translated Text from Indonesian into English - Marwan Tanuwijaya; Aditya Cahyo Nugroho; Pratama Ahdi; Novita Dewi (Indonesian Journal of English Language Studies (IJELS), 2016)
The main aspect of translation is how one’s expression in   one language is replaced with an equivalent representation in another language. The representation should be equivalent in terms of its stylistic, referential, and linguistic features. Whether there is a need for a translation text to be classified as "weak," "fair" or "good," its acceptability and the means of determining it as well as how to improve one’s translation quality were what we investigated in this article. National and international translation standards now exist, but there are no generally accepted objective criteria for evaluating the quality of translation. Therefore, such an assessment is needed to reveal the quality of the translation of a text from Indonesian into English. This article aimed to assess it using an alternative instrument and suggestions on how to improve translation quality which the authors adapted from NAATI (National Accreditation Authority of Translators and Interpreters). They adopted the stylistic, referential, and linguistic components of NAATI’s translation quality assessment. Based on the limited data that they had, a number of improvement procedures were recommended.